Comparison of the safety and efficacy of radiofrequency thermocoagulation with percutaneous balloon compression for treating trigeminal neuralgia: a systematic review and meta-analysis - Wu, Zeyu; Zhao, Yongming; Liu, Jiang; Fan, Yiyue; Yang, Ying (Frontiers in Neurology, 2023)
Objective: This study aimed to systematically assess the efficacy and complications of radiofrequency thermocoagulation (RFT) and percutaneous balloon compression (PBC) for treating trigeminal neuralgia (TN). Methods: the literature was strictly screened using specific inclusion and exclusion criteria. The RevMan 5.4 software was used for data processing and meta-analysis.Results: Overall, 16 studies with 3,326 patients were included. The results of meta-analysis revealed that no significant difference was present between the two groups in terms of the rate of efficacy immediately after surgery, 1 month after surgery, and 3 months after surgery (odds ratio [OR] = 0.73, 95% confidence interval[CI] 0.35-1.54, P = 0.41; OR = 0.41, 95% CI 0.13-1.32, P = 0.13; OR = 0.40, 95% CI 0.10-1.60, P = 0.20); however, at 12 months after surgery, the difference was statistically significant (OR = 0.27, 95% CI 0.10-0.75, P = 0.01). Notably, there was no significant difference in the postoperative sleep quality index between the two groups immediately after surgery and 1 month after surgery (SMD = −0.01, 95% CI −2.47 to 2.44, P = 0.99; SMD = 0.14, 95% CI −3.95 to 4.22, P = 0.95). Further, statistically significant differences were observed between the two groups in the incidence of postoperative masticatory muscle strength decline and oral herpes (OR = 0.37; 95% CI 0.21-0.63, P = 0.0003; OR = 0.25, 95% CI 0.10-0.61, P = 0.003). In addition, a statistically significant difference was found in the recurrence rate at 1-year follow-up (OR = 2.23, 95% CI 1.03-4.81, P = 0.04); however, no statistically significant differences were found in the recurrence rate at the 2-year follow-up (OR = 1.95, 95% CI 0.33-11.59, P = 0.46).In the treatment of TN, both RFT and PBC can achieve good short-term efficacy, and no significant differences were noted between the outcomes of the two approaches. Compared with RFT, PBC may result in a lower pain score and recurrence rate in the medium and long terms, but it is a higher incidence of cold sores, and the decrease of masticatory muscle strength is more obvious.